PENERAPAN METODE BASMALAH DALAM MENINGKATKAN MOTIVASI BELAJAR MATA PELAJARAN AL-QUR’AN HADIST DI MTSN 4 BONE - Jalingga, Emen Yusuf; Thahir, Ilyas; Sampurno, Bambang; Bunyamin, Andi; Mustamin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the implementation of the Basmalah method (Learning the Qur’an While Playing for More Enjoyable and Easier Learning) in improving students’ motivation and learning outcomes in the Qur’an Hadith subject for class IX.C at MTsN 4 Bone. This research employed Classroom Action Research (CAR) conducted in two cycles, where each cycle consisted of planning, action, observation, and reflection stages. The subjects of this study were 26 students. Data collection techniques used were observation and tests. The results showed that the implementation of the Basmalah method improved students’ motivation and learning outcomes. This can be seen from the increase in learning motivation from 60.2% in the pre-cycle to 74.2% in cycle I and further increased to 85.5% in cycle II. In addition, students’ learning outcomes also improved, with the average score increasing from 59.8 in the pre-cycle to 77.1 in cycle I and 81.7 in cycle II. These improvements indicate that the Basmalah method is effective in creating an active, enjoyable, and meaningful learning process. Thus, it can be concluded that the BASMALAH method is effective in improving students’ motivation and learning outcomes in the Qur’an Hadith subject.